DEFENDING SPACES, PREVENTING CONFLICTS: The Politics of Identity Representation in the Nahdliyin Mosques in Malang Raya (JOURNAL OF INDONESIAN ISLAM, 2020)
Contemporary dynamics among Islamic groups in Indonesia have affected aspects of Indonesian mosque architecture. One striking issue is the expropriation attempts against Nahdliyin mosques by certain groups deemed radical. The issue has drawn attention from the majority of Nahdliyin people through the Nahdlatul Ulama’s official media. This study explores preventive actions taken by the Nahdliyin based on their shared-perspective towards the issue. Text and visual analyses are conducted based on the data of six chosen mosques in Malang Raya, East Java – a region with a great basis of the Nahdliyin, as well as the melting pot for various Islamic groups. The result shows that there are serious attempts of the surrounding communities to affirm their identity on their mosques. Iconographic and symbolic elements are applied to the mosque buildings to prevent mosques from being expropriated by other groups considered as hardliners. It further suggests an ambivalence where some pros and cons among the Nahdliyin themselves have occurred in terms of positive or negative impacts of the emergence of explicit identity on their mosques. Nevertheless, understanding the concept of shared-identity between a mosque and its surrounding community is an important basis to maintain peace and tolerance in the religious life of Muslim societies.